The role of human brands in consumer attitude formation: Anthropomorphized messages and brand authenticity - Hee-Eun Han; Ge-Qi Cui; ChangHyun Jin (Cogent Business & Management, 2021)
The purpose of the study attempts to assess consumer reactions by classifying anthropomorphized messages according to the authenticity of a human brand with which they are associated. And also the study to investigate the causal relationship between attributions of human brand and consumer-brand relationships, brand attitudes, and purchase intention. An experimental design was used to test the hypotheses. To examine factors that can help brands achieve marketing goals through the use of human brands, this study developed research hypotheses and a structural model by focusing on the consumer information-treating process based on the authenticity of a human brand and message type. The results indicate the existence of a between-group difference with respect to anthropomorphized messages as opposed to non-anthropomorphized messages as well as levels of brand authenticity. An interaction effect was observed for the consumer-brand relationship and attitudes toward a brand. In the main effect analysis, anthropomorphized messages induced a stronger consumer-brand relationship, more positive attitudes toward a brand, and stronger purchase intention for a brand. The results of a path analysis indicated that three dimensions of human brand attributions positively affect consumer-brand relationships. This study provides a new approach to the use of anthropomorphized messages by focusing on the relationship between advertising models and messages. As a result, positive effects can be expected as identification with an advertising model increases.
Keywords: 650; Human brand; Celebrity; Consumer-brand relationship; Anthropomorphized; Brand authenticity